Transmission electron microscopic observation of body cuticle structures of phoretic and parasitic stages of Parasitaphelenchinae nematodes - Ekino, Taisuke; Yoshiga, Toyoshi; Takeuchi-Kaneko, Yuko; Kanzaki, Natsumi (PloS one, 2017)
Using transmission electron microscopy, we examined the body cuticle ultrastructures of phoretic and parasitic stages of the parasitaphelenchid nematodes Bursaphelenchus xylophilus, B. conicaudatus, B. luxuriosae, B. rainulfi; an unidentified Bursaphelenchus species, and an unidentified Parasitaphelenchus species. Nematode body cuticles usually consist of three zones, a cortical zone, a median zone, and a basal zone. The phoretic stages of Bursaphelenchus spp., isolated from the tracheal systems of longhorn beetles or the elytra of bark beetles, have a thick and radially striated basal zone. In contrast, the parasitic stage of Parasitaphelenchus sp., isolated from bark beetle hemocoel, has no radial striations in the basal zone. This difference probably reflects the peculiar ecological characteristics of the phoretic stage. A well-developed basal radially striated zone, composed of very closely linked proteins, is the zone closest to the body wall muscle. Therefore, the striation is necessary for the phoretic species to be able to seek, enter, and depart from host/carrier insects, but is not essential for internal parasites in parasitaphelenchid nematodes. Phylogenetic relationships inferred from near-full-length small subunit ribosomal RNA sequences suggest that the cuticle structures of parasitic species have apomorphic characters, e.g., lack of striation in the basal zone, concurrent with the evolution of insect parasitism from a phoretic life history.